Biaya Pendidikan Sebagai Nafkah Anak dalam Islam (Studi Fenomelogi Keluarga Petani di Kabupaten Jember) - Syarofi, Muhammad; Rusmini, Rusmini (INAIFAS Press, 2021)
ABSTRACT A family head as a household leader has a liability in providing a living for his wife and children, according to their respective needs. This income is not only limited to physical needs, but also spiritual needs, namely the cost of education, in order for the survival of the child in the future and be able to continue the struggle and substitute for his parents if he died. This paper examines one of the families who are able to provide a living for one of their children to level 3 doctoral program, with the main source of income from the agricultural sector. The direction of writing this research method is qualitative through a phenomenological approach, with data extraction using a semi-structured interview method. The results of the study showed that the breadworthiness given by the two parents to their children directed at the cost of education, as supporting their survival in the future, while being able to continue the struggle of both parents and could become a replacement for her parents if they died.